Future of photovoltaic technologies: A comprehensive review. (October 2021) - Ghosh, Santosh; Yadav, Ranjana
Abstract: Presently, the world is going through a euphoric rush to install photovoltaic (PV) devices in deserts, over water bodies, on rooftops of houses, vehicles, and parking spaces, and many other applications. The cumulative PV installation is estimated to have crossed 600 GW globally to date and is expected to cross 4500 GW by 2050 due to sustained investment and continual innovation in technology, project financing, and execution. This article presents a critical and comprehensive review of the wide spectrum of present and future PV technologies, not only in terms of their performance but also in terms of the aspects of their end-of-life waste management and ecotoxicity, which have been largely neglected by the researchers and policymakers. The global status of the regulatory framework is reviewed as well, with regard to the life cycle management of PV waste. And It is found that presently, the world is very poorly equipped with regulatory frameworks to deal with massive PV waste (about 78 million tonnes), expected to be generated by 2050. Based on the findings, an immediate and disruptive paradigm shift is proposed in the policy framework, from the promotion of new PV installation to life cycle management of PV assets.